Pengaruh Disiplin Kerja, Beban Kerja dan Gaji Terhadap Retensi Karyawan Pada PT. Yasuriang Samudera Rezeki Belawan - Hutapea, Kartini Meliana; Risal, Taufiq (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the effect of work discipline, workload, and salary on employee retention at PT. Yasuriang Samudera Rezeki Belawan. This study employed quantitative research. The data sources used were primary and secondary data sources. The population was comprised of PT. Yasuriang Samudera Rezeki employees. The sample size was 128 respondents. Data analysis techniques used in this study included descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. Based on the partial test results, it was found that work discipline had a positive and significant effect on employee retention, with a t-value of 4.906 > t-table 1.979. Furthermore, workload did not have a positive and significant effect on employee retention, with a t-value of 1.224 < t-table 1.979. Similarly, salary had a positive and significant effect on employee retention, with a t-value of 3.572 > t-table 1.979. Based on the results of the simultaneous test, it was found that f count > f table, i.e., 33.170 > 2.68. Therefore, it can be concluded that the variables of work discipline (X1), workload (X2), and salary (X3) collectively have a positive and significant effect on employee retention at PT. Yasuriang Samudera Rezeki.